Waste production on terraces with PVC sheets and study of their CO2 emissions = Producción de residuos en azoteas con láminas de PVC y estudio de sus emisiones de CO2 - Manuel J. Carretero Ayuso; Gonzalo Sánchez Barroso; Justo Garcia Sanz Calcedo; Miguel Gómez Chaparro (Building & Management, 2019)
The objective of the analysis presented is to compare the environmental impact of different solutions of roofs according to the CO2 emissions they release into the atmosphere (in kg/m2), as well as the generation of waste (in kg/m2), from the nature of their different constituent layers. For this purpose, waste has been grouped under two criteria: waste per placement and waste per packaging. The analysed roofs are all with a slope of less than 5% (i.e. flat roofs); in order to be more specific, the typologies that were inverted type have been chosen (which means that the insulation was arranged over the waterproofing), given that they are the most commonly used. In addition, only variants with the waterproofing layer consisting of a PVC membrane and three different types of roofs were compared: non-trafficable flat roof finished with gravel (Type A), garden flat roof (Type B) and walkable flat roof with fixed tile flooring (Type C). To make this comparison, the BEDEC database of Instituto de Tecnología de la Construcción (ITEC) has been used and the characterisation of the constituent layers has been carried out according with the LER codes (European Waste List). In addition, life cycle analysis techniques have been used according to the UNE-EN-ISO-14040:2006 and UNE-EN-ISO-14044:2006 standards. It was verified that the least efficient roof with the highest environmental impact values corresponds to Type C.